2015
DOI: 10.1007/s11657-015-0240-5
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of osteoporosis-related femoral fractures and economic burden in Saudi Arabia

Abstract: Osteoporosis-related femoral fractures in Saudi Arabia are significant causes of morbidity besides incurring economic burden. We believe that a National Fracture Registry needs to be established, and osteoporosis awareness programs should be instituted in every part of Saudi Arabia so that these patients can be diagnosed early and treated appropriately to reduce both the number of fractures and the economic burden of the fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 13 publications
0
26
1
Order By: Relevance
“…Osteoporosis along with osteopenia is responsible for fragility fractures, which contribute to the increasing morbidity and mortality rates. A previous study published in 2015 showed that the proximal femoral fracture incidence is 5.89 per 1000 individuals, and the estimated lifetime spending for fragility femoral fractures was 9.34 billion USD [2931]. Moreover, 17 billion USD was the total healthcare cost of two million cases of fractures in the USA alone, and such cost is calculated to increase to 25 billion USD in 2025 because of an estimated 50% increase in fracture incidence [32].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis along with osteopenia is responsible for fragility fractures, which contribute to the increasing morbidity and mortality rates. A previous study published in 2015 showed that the proximal femoral fracture incidence is 5.89 per 1000 individuals, and the estimated lifetime spending for fragility femoral fractures was 9.34 billion USD [2931]. Moreover, 17 billion USD was the total healthcare cost of two million cases of fractures in the USA alone, and such cost is calculated to increase to 25 billion USD in 2025 because of an estimated 50% increase in fracture incidence [32].…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 A recent study revealed that the incidence of proximal femoral fractures in a Saudi population of patients aged ≥50 years was 5.89/1000. 8 Very high mortality rates associated with fragility hip fractures have been reported in developed countries, with 5% to 10% of affecting patients dying within 1 month of fracture and 20% to 30% dying within 1 year. 9 , 10 In 2013, Diamantopoulos et al.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] It was reported that direct and indirect costs of osteoporosis-related hip fractures yearly in Saudi Arabia reached Saudi riyals 2.359 billion and is projected that the lifetime costs of this single osteoporosis-related hip fracture by 2025 will reach SR35.0028 billion ($9.34 billion). [ 8 ] If the patients are screened earlier and treated appropriately as per the US database of 2011, it will cost $2 billion, and if left untreated, once the fragility fractures are treated, the cost goes eight times to $16 billion. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] In Saudi Arabia, a neighbor of the Kingdom of Bahrain, the incidence of fractures rose from 2.9/1000 of the population in Riyadh[ 7 ] to 5.8/1000 in the Eastern Province. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%